2023
DOI: 10.1186/s40538-022-00362-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of decomposition agent application and schedule in wheat straw return practice on soil quality and crop yield

Abstract: Straw return is a beneficial agricultural practice but mechanisms and information on microbial community alterations initiated by decomposed straw and promotion of soil nutritive content and conservation is still not adequately understood. Therefore, the study applied molecular, bioinformatics, chemical and plant yield analysis to determine the effect of wheat straw return and decomposing agent on soil, fungi and crop yield characteristics under wheat biomass return with and without the inclusion of the decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The results of this study demonstrate that different straw-returning measures, including straw mulching, straw incorporation, and biochar application, have a significant impact on increasing soil carbon, nitrogen, phosphorus, and potassium levels (Tables 1 and 2). The direct effect of returning straw is to raise soil nutrient levels by introducing mineral nutrients and organic matter into the soil [29,30]. Straw and biochar, both rich in organic carbon, increase the organic matter content in the soil.…”
Section: Effects Of Different Straw Returning Measures On Soil Nutrientsmentioning
confidence: 99%
“…The results of this study demonstrate that different straw-returning measures, including straw mulching, straw incorporation, and biochar application, have a significant impact on increasing soil carbon, nitrogen, phosphorus, and potassium levels (Tables 1 and 2). The direct effect of returning straw is to raise soil nutrient levels by introducing mineral nutrients and organic matter into the soil [29,30]. Straw and biochar, both rich in organic carbon, increase the organic matter content in the soil.…”
Section: Effects Of Different Straw Returning Measures On Soil Nutrientsmentioning
confidence: 99%
“…Previous studies have demonstrated the positive impact of straw incorporation on soil quality and subsequent crop yield improvement [73]. In the present study, the MDS-SQI for the four treatments followed the order of C7 > C3 > F3 > F7.…”
Section: Mds-based Soil Quality Evaluationmentioning
confidence: 59%
“…Evidence has suggested that slow straw decomposition may reduce seedling quality [101]. Thus, the application of decomposition agents after SR is required to improve straw utilization rates at this stage [102]. Notably, although decomposition agents promote straw decomposition, this rapid decomposition accelerates N fixation by soil microorganisms and reduces soil N effectiveness.…”
Section: Sr and Associated Challengesmentioning
confidence: 99%